"Teachers are works in progress": A mixed methods study of teaching residents' beliefs and articulations of teaching for social justice. (October 2016) - Reagan, Emilie Mitescu; Chen, Crystal; Vernikoff, Laura
Abstract: Teacher candidates' beliefs about teaching for social justice affect the ways in which they act with students, schools, and communities. There is a growing body of research on teacher candidates' beliefs of teaching for social justice, however there is limited research on larger samples over the course of teacher preparation. This mixed method study examines the beliefs and articulations of teaching for social justice of two cohorts of teaching residents who completed an urban teacher residency program. Findings suggest that residents developed nuanced ways of articulating and generally left the program endorsing ideas related to teaching for social justice. Highlights: Teacher candidates beliefs of teaching for social justice are examined. Candidates shifted their ideas of teaching for social justice during preparation. Candidates' beliefs generally held strong beliefs about teaching for social justice. Further research is needed to explore teaching practice of novice teachers.